1994
DOI: 10.1002/jnr.490370314
|View full text |Cite
|
Sign up to set email alerts
|

Role for the stem cell factor/KIT complex in schwann cell neoplasia and mast cell proliferation associated with neurofibromatosis

Abstract: Schwann cells are the primary cell type in the disfiguring lesions associated with neurofibromatosis type 1 (NF-1). These lesions also contain abnormally high numbers of mast cells, a cell type which develops in response to stem cell factor. We report here that neonatal and adult rat and human Schwann cells, as well as a transfected rat Schwann cell line and a human Schwannoma line derived from an NF-1 patient, all produced stem cell factor mRNA and protein. In coculture experiments, surface expression of stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 66 publications
5
70
0
Order By: Relevance
“…51 Previous studies have suggested that mast cells may induce or contribute to tumor formation in Nf1 mutant mouse models. 11,52 We found that mast cells infiltrate sNF96.2 xenografted tumors in scid mice, and do so in a manner similar to mast cell infiltrates seen in human NF1 MPNSTs. 53 Mast cells may be important contributors to NF1 tumor angiogenesis and progression in the tumor environment.…”
Section: Discussionsupporting
confidence: 55%
“…51 Previous studies have suggested that mast cells may induce or contribute to tumor formation in Nf1 mutant mouse models. 11,52 We found that mast cells infiltrate sNF96.2 xenografted tumors in scid mice, and do so in a manner similar to mast cell infiltrates seen in human NF1 MPNSTs. 53 Mast cells may be important contributors to NF1 tumor angiogenesis and progression in the tumor environment.…”
Section: Discussionsupporting
confidence: 55%
“…Although the nature of these paracrine signaling factors is incompletely understood, there is good evidence that at least one of them is stem cell factor (SCF, also known as Kit ligand), a protein that promotes the migration, survival, maturation, and activation of mast cells. 35,36 NF1 loss enhances SCF expression, with NF1 À/À Schwann cells secreting sixfold higher levels of SCF than NF1 þ/À or wild-type Schwann cells. 37 Intriguingly, changes in NF1 copy number also affects mast cell physiology; NF1 þ/À mast cells show enhanced proliferation, survival, and migration when challenged with SCF.…”
Section: Oncogenomics In Mpnst Modelsmentioning
confidence: 96%
“…SC/nervous system interdependence leads to mutual disturbances. For example, experimental and genetically determined SC diseases often result in axonal pathology (Ryan et al 1994). Mycobacterium leprae, the causative agent of leprosy, presents a unique characteristic among human pathogens in its ability to invade and survive inside SC (Rambukkana et al 1997).…”
mentioning
confidence: 99%